Rendering assemblage dialectical - Campbell, Stephen (2022)
Within anthropology, assemblage theory has achieved broad disciplinary traction, yet the theory’s philosophical premises are rarely explored. This article therefore revisits the Deleuzian notion of difference that underpins assemblage theory as a step towards rendering the theory more consonant with a relational anthropology. In place of Gilles Deleuze and Félix Guattari’s conception of discrete elements related only externally to each other within an assemblage, I propose a dialectical conception, whereby assemblage is taken to be a heterogeneous ensemble whose constituent elements also relate to each other internally. To arrive at this understanding, I examine the dialectical logic of Theodore Adorno. I then consider the implications of a dialectical notion of assemblage for recent work on the anthropology of capitalism.